Percolative cobalt/silicon nitride composites with tunable negative electromagnetic parameters. Issue 86 (31st August 2016) - Zhang, Zi-dong; Cheng, Chuan-bing; Han, Xu
Abstract : A 3D fishnet structure is formed in the Co/Si3 N4 composites to obtain tunable negative electromagnetic parameters from 550 MHz to 1 GHz, which have potential applications in antennas, electromagnetic shielding and band-pass filter. Abstract : In this paper, the relationship between the microstructures and electromagnetic properties of cobalt/silicon nitride (Co/Si3 N4 ) composites synthesized by an impregnation–calcination process are discussed. The enhanced interconnectivity of cobalt particles led to the appearance of percolation phenomenon and the change of conductive mechanism from hopping conduction to metal-like conduction. The composites above percolation threshold exhibited the negative permittivity and negative permeability behavior, which were mainly ascribed to the plasma oscillation of free electrons and the diamagnetic responses of conductive cobalt network, respectively. The frequency region and magnitude of such negative electromagnetic parameters closely associated with the cobalt content. When the cobalt content reached 35 wt%, simultaneous negative permittivity and negative permeability were realized in the frequency range from 550 MHz to 1 GHz. The experimental exploration of Co/Si3 N4 composites by tailoring compositions and microstructures has great significance on the development of tunable negative electromagnetic parameter materials.